Positive electrode lithium-supplementing composite material with core-shell structure and preparation method and application of positive electrode lithium-supplementing composite material
The positive electrode lithium supplement material is coated by amphiphilic compounds with a specific structure, forming an efficient single-molecular layer cladding layer, solving the environmental stability and lithium ion conductivity of the positive electrode material, and significantly improving the electrochemical performance of lithium-ion batteries and cycle life.
Patent Information
- Application Number
- CN202411383953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing positive electrode lithium supplement material has poor environmental stability during storage and processing, resulting in high processing costs of lithium-ion batteries. The lithium-ion conduction capacity of the physical barrier layer of traditional coating technology has poor lithium-ion conduction capabilities, resulting in battery capacity loss and polarization increase. big.
The positive electrode lithium supplement material is coated with amphiphilic compounds with a specific structure to form a thin and dense single-molecular layer cladding layer. The hydrophilic head combines with the alkaline groups on the surface of the positive electrode material, and the hydrophobic tail is formed. Hydrophobic membrane, improving electrochemical stability and lithium ion conduction properties.
It significantly reduces the residual alkali on the surface of the positive electrode lithium supplement material, improves electrochemical stability and durability, enhances lithium ion conductivity, reduces interface transmission impedance, and extends the cycle life of lithium ion batteries.
Smart Images

Figure CN119253096A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium supplement material, and in particular relates to a positive electrode lithium supplement composite material with a core-shell structure, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, low cost and long service life. They are also high-quality carriers of clean energy (such as wind energy and solar energy), so they can become ideal power sources in the field of electric vehicles. However, due to people's anxiety about the range of cars, the market urgently needs LIBs that can provide higher energy density. Based on this, the addition of lithium replenishing materials can not only solve the problem of low battery energy density, but also the research and development of lithium replenishing materials has more cost advantages. The current negative electrode lithium replenishment technology has relatively harsh conditions and requires a very dry environment. Compared with the negative electrode lithium replenishment technology, the positive electrode lithium replenishment technology can mix the lithium replenisher with the positive electrode material during the slurry mixing stage, without the need for complex processes, which is convenient for industrial production.
[0003] However, the positive electrode lithium supplement materials currently used have poor environmental stability during storage and processing, resulting in high processing costs for lithium-ion batteries. Therefore, it is urgent to solve the environmental stability problem of positive electrode lithium supplement materials to reduce the production cost of lithium-ion batteries. To this end, the prior art discloses coating the positive electrode lithium supplement materials with a hydrophobic layer, thereby further improving the environmental stability of the positive electrode lithium supplement materials.
[0004] Most of the technical means disclosed in the prior art are to coat a physical barrier layer on the surface of the positive electrode lithium supplement material. After being stored under ambient conditions, the positive electrode lithium supplement material is easy to react with water or carbon dioxide, resulting in the loss of capacity of the positive electrode material, and the polarization inside the battery increases and eventually fails. This is because the physical barrier layer has poor lithium ion conductivity and protection of the positive electrode material. In addition, the current coating technology usually uses high-temperature solid phase or atomic vapor deposition (ALD) for coating, so that the formed coating layer is thicker, or its process cost is high, and the thickness will change due to the change of the morphology of the positive electrode material, resulting in uneven thickness of the coating layer.
[0005] Therefore, in this field, there is an urgent need to develop a positive electrode lithium supplement composite material to solve the above problems. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a positive electrode lithium supplement composite material with a core-shell structure and its preparation method and application. The present invention adjusts the composition and structure of the positive electrode lithium supplement composite material so that the formed coating layer has both good environmental stability and ion conductivity, especially the formed monolayer coating layer has the characteristics of being thin, dense, and uniform, and the thickness will not change due to the morphology change of the positive electrode lithium supplement material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a positive electrode lithium supplement composite material having a core-shell structure, wherein the positive electrode lithium supplement composite material having a core-shell structure comprises a positive electrode lithium supplement core material and a monomolecular layer coating layer coated on the surface of the positive electrode lithium supplement core material;
[0009] The material of the monomolecular coating layer includes an amphiphilic compound, and the amphiphilic compound includes a hydrophilic head and a hydrophobic tail. The structural formula of the amphiphilic compound is shown in Formula I:
[0010] XYZ
[0011] Formula I;
[0012] Wherein, the structure of X contains any one or a combination of at least two of a carboxylate group, a sulfonate group, a sulfate group or a silane group;
[0013] Y is selected from at least one of a single bond, a hydrocarbon group or a nitrogen heterocycle;
[0014] Z is at least one selected from a substituted or unsubstituted hydrocarbon group, a substituted or unsubstituted thiol hydrocarbon group, or a substituted or unsubstituted aryl group.
[0015] On the one hand, the present invention coats environmentally sensitive positive lithium replenisher materials by using amphiphilic compounds with specific structures, wherein the hydrophilic head is combined with the surface alkaline groups of the positive lithium replenisher material, and the hydrophobic tail is facing the outside world, and finally a hydrophobic film with good chemical stability can be formed on the surface of the positive lithium replenisher material, thereby preventing water molecules and corrosive substances from directly contacting the positive lithium replenisher material, and improving the electrochemical stability and durability of the positive lithium replenisher composite material. Compared with the traditional solid phase coating, it is thinner and more uniform, so the conductivity is higher. Specifically, the positive lithium replenisher composite material with a core-shell structure provided by the present invention has a surface residual alkali amount reduced by about 11.2% compared with the uncoated positive lithium replenisher material after being placed for 5 days.
[0016] On the other hand, compared with the traditional hydrophobic physical coating layer, the hydrophobic monolayer coating layer formed by the present invention has the advantages of thinner thickness, uniform distribution and density, and its own lithium ion conductivity is better. In addition, since inorganic salt components are generated on the surface of the coating layer, the interfacial transmission impedance of the surface of the positive electrode lithium supplement material after coating is reduced, and it has better electrochemical stability.
[0017] Preferably, the structure of X comprises a combination of a silane group and a sulfonate group, or a combination of a carboxylate group and a sulfonate group.
[0018] Preferably, Y is selected from a single bond or an alkyl group.
[0019] Preferably, Z is selected from at least one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted sulfanyl group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, and a substituted or unsubstituted phenylsilyl group.
[0020] Preferably, the substituted group includes at least one of a halogen atom, a nitrogen heterocycle, an aryl group or an alkyl group.
[0021] Preferably, the amphiphilic compound is selected from any one or a combination of at least two of polyphenylmethylsilane, phenyltri(trimethylsiloxy)silane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, pentafluorononyltrimethoxysilane, pentafluorononyltriethoxysilane, tridecafluorooctyltrimethoxysilane or tridecafluorooctyltriethoxysilane.
[0022] Preferably, the amphiphilic compound is selected from any one or a combination of at least two of 3-fluorobenzene methane sulfonic acid, benzene sulfonic acid, 4-fluorobenzene sulfonic acid, dodecylbenzene sulfonic acid, undecylbenzene sulfonic acid, decanylbenzene sulfonic acid, pentafluorobenzene sulfonic acid, perfluorohexyl sulfonic acid, sodium dodecyl sulfate, sodium tetradecyl sulfate, ammonium dodecyl sulfate or sodium decyl sulfate.
[0023] Preferably, the amphiphilic compound is selected from any one or a combination of at least two of stearic acid, tryptophan, diphenylacetic acid, 2-[(difluoromethyl)sulfanyl]pyridine-3-carboxylic acid or (2S,4R)-4-((tert-butyldiphenylsilyl)oxy)pyrrolidine-2-carboxylic acid.
[0024] Preferably, when the amphiphilic compound includes a combination of fluorinated silane molecules and alkyl sulfonic acid molecules, the mass ratio of the fluorinated silane molecules to the alkyl sulfonic acid molecules is (60-90):(10-40), preferably (65-85):(15-35), for example, it can be 60:40, 62:38, 65:35, 68:32, 70:30, 72:28, 75:25, 78:22, 80:20, 82:18, 85:15, 88:12, 90:10, etc. The present invention regulates the mass ratio of fluorinated silane molecules and alkyl sulfonic acid molecules so that the positive electrode lithium supplement composite material has better hydrophobic effect and smaller polarization.
[0025] In the present invention, by regulating the types of groups of the hydrophilic head and the hydrophobic tail in the amphiphilic compound, the hydrophilic head is combined with the basic groups on the surface of the positive electrode lithium supplement material, making the coating more uniform and making the hydrophobic tail have a stronger hydrophobic effect.
[0026] Preferably, the chemical formula of the core material of the positive electrode lithium supplement is Li a M x N 1-x O c , wherein 2≤a≤6, 0≤x≤1, 1≤c≤6, and M includes Fe or Ni, and N includes at least one of Mg, Al, Si, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Sn or W.
[0027] In the present invention, the a can be, for example, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, etc.; the x can be, for example, 0, 0.2, 0.5, 0.8, 1, etc.; the c can be, for example, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, etc.
[0028] Preferably, the hydrophilic head is at least partially bonded to the surface of the positive electrode lithium supplement core material.
[0029] Preferably, the mass ratio of the material of the monolayer coating layer to the core material of the positive electrode lithium supplement agent is (0.001-0.05):1, preferably (0.005-0.03):1, for example, it can be 0.001:1, 0.002:1, 0.005:1, 0.008:1, 0.01:1, 0.012:1, 0.015:1, 0.018:1, 0.02:1, 0.022:1, 0.025:1, 0.028:1, 0.03:1, 0.032:1, 0.035:1, 0.038:1, 0.04:1, 0.042:1, 0.045:1, 0.048:1, 0.05:1, etc. The present invention adjusts the mass ratio of the material of the monomolecular coating layer to the core material of the positive electrode lithium supplement agent, so that the positive electrode lithium supplement agent composite material has better hydrophobic effect and smaller polarization. If the content of the material of the monomolecular coating layer is high, it will have a higher polarization, otherwise it will have a poorer hydrophobic effect.
[0030] In the present invention, the thickness of the monolayer coating layer is 2-10 nm, for example, it can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0031] In a second aspect, the present invention provides a method for preparing a positive electrode lithium supplement composite material having a core-shell structure according to the first aspect, the method comprising the following steps:
[0032] The amphiphilic compound is coated on the positive electrode lithium replenishing agent material by a liquid phase method and / or a gas phase method to obtain the positive electrode lithium replenishing composite material with a core-shell structure, wherein the amphiphilic compound includes a hydrophilic head and a hydrophobic tail.
[0033] The present invention uses a simple molecular self-assembly method for coating, and finally obtains an ultra-thin monomolecular coating layer, so it has high ionic conductivity and uniformity, and does not change in thickness due to changes in the morphology of the material. In addition, the preparation method provided by the present invention is simple to operate and easy to mass produce.
[0034] In the present invention, before coating the positive electrode lithium replenisher material with the amphiphilic compound by liquid phase method and / or gas phase method, the positive electrode lithium replenisher material may be subjected to high temperature heating treatment (eg, 100-300° C.) to remove the adsorbed moisture on the surface.
[0035] Preferably, the liquid phase method comprises mixing an amphiphilic compound, a positive electrode lithium replenishing agent material and a solvent, and removing the solvent after the reaction to obtain the positive electrode lithium replenishing composite material having a core-shell structure.
[0036] In the present invention, the method for removing the solvent exemplarily includes a drying treatment, and the drying treatment includes a vacuum drying treatment or a spray drying treatment, the temperature of the spray drying treatment is 60-120° C., and the gas is dry air or an inert atmosphere.
[0037] Furthermore, the present invention provides an exemplary liquid phase preparation method, which comprises the following steps:
[0038] dissolving the amphiphilic compound in a solvent to form a solution;
[0039] The positive electrode lithium supplement material is poured into the solution and stirred to allow the two to fully contact and react. The reaction time is 3 hours. After the reaction is completed, a suction flask is used for filtration to remove the solvent and unreacted organic molecules.
[0040] The collected materials are placed in a vacuum oven under an inert atmosphere and dried at 70° C. for 2 hours. The collected dry powder is a positive electrode lithium supplement composite material with a core-shell structure.
[0041] In the present invention, the solvent exemplarily includes any one or a combination of two or more of N-methylpyrrolidone, ethanol, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide or acetone, and the solvent used can be any one as long as it can dissolve the above-mentioned amphiphilic compound and the positive electrode lithium replenisher material, and the present invention is not limited to this.
[0042] Preferably, the gas phase method comprises placing the positive electrode lithium replenisher material in a system containing amphiphilic compound vapor, and cooling the system to form the positive electrode lithium replenisher composite material having a core-shell structure.
[0043] Furthermore, the present invention provides an exemplary gas phase preparation method, which comprises the following steps:
[0044] The amphiphilic compound is placed at the bottom of a sealed container, and the positive electrode lithium supplement material powder is suspended above the amphiphilic compound;
[0045] The above container is placed in an oven, heated to 120°C for 6 hours, so that the amphiphilic compound is volatilized by heat, thereby spontaneously growing on the surface of the positive electrode lithium replenisher material to form a single molecule coating layer; after cooling to room temperature, the internal powder is stirred, and then heating, cooling and stirring are performed again, and the process is repeated 2-4 times to complete the coating, and a positive electrode lithium replenisher composite material with a core-shell structure is collected.
[0046] Furthermore, the present invention provides another exemplary gas phase preparation method, which comprises the following steps:
[0047] The amphiphilic compound is placed in a sealed container, and the positive electrode lithium supplement material powder is placed in a porcelain boat, which is wrapped with an aluminum-plastic film with a small opening in the upwind direction.
[0048] In an inert atmosphere, the device was placed in a tubular furnace with a heating temperature of 90°C and a heating time of 5 hours, wherein the wind direction of the inert atmosphere was parallel to the horizontal plane of the device, so that the amphiphilic compound was volatilized by heat and spontaneously grew on the surface of the material to form a coating layer, and a positive electrode lithium supplement composite material with a core-shell structure was collected.
[0049] In a third aspect, the present invention provides a positive electrode, which includes a positive electrode active material and a lithium supplement material, wherein the lithium supplement material includes the positive electrode lithium supplement composite material with a core-shell structure according to the first aspect.
[0050] Preferably, based on the total mass of the positive electrode active material as 100%, the mass percentage of the lithium supplement material is 2wt.% to 8wt.%, for example, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, 5.5wt.%, 6wt.%, 6.5wt.%, 7wt.%, 7.5wt.%, 8wt.%, etc. The present invention adjusts the mass percentage of the lithium supplement material so that the prepared secondary battery has a longer cycle life.
[0051] In a fourth aspect, the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode according to the third aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention provides a positive electrode lithium replenishment composite material with a core-shell structure. On the one hand, the present invention uses an amphiphilic compound with a specific structure to coat an environmentally sensitive positive electrode lithium replenishment material, wherein the hydrophilic head is combined with the surface alkaline group of the positive electrode lithium replenishment material, and the hydrophobic tail is facing the outside world, and finally a hydrophobic film with good chemical stability can be formed on the surface of the positive electrode lithium replenishment material, thereby preventing water molecules and corrosive substances from directly contacting the positive electrode lithium replenishment material, and improving the electrochemical stability and durability of the positive electrode lithium replenishment composite material. Compared with the traditional solid phase coating, it is thinner and more uniform, so the conductivity is higher. Specifically, the positive electrode lithium replenishment composite material with a core-shell structure provided by the present invention has a surface residual alkali amount reduced by about 11.2% compared with the uncoated positive electrode lithium replenishment material after being placed for 5 days.
[0054] On the other hand, compared with the traditional hydrophobic physical coating layer, the hydrophobic monolayer coating layer formed by the present invention has the advantages of thinner thickness, uniform distribution and density, and its own lithium ion conductivity is better. In addition, since inorganic salt components are generated on the surface of the coating layer, the interfacial transmission impedance of the surface of the positive electrode lithium supplement material after coating is reduced, and it has better electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a flow chart for preparing the positive electrode lithium-supplementing composite material with a core-shell structure in Example 1;
[0056] Figure 2 This is a SEM image of the positive electrode lithium supplement composite material with a core-shell structure in Example 1;
[0057] Figure 3 This is a flow chart for preparing the positive electrode lithium-supplementing composite material with a core-shell structure in Example 2;
[0058] Figure 4 The flowchart of the preparation of the positive electrode lithium supplement composite material with core-shell structure in Example 3;
[0059] Figure 5 A comparison chart of the residual alkali content of the positive electrode lithium-supplementing composite material with a core-shell structure provided in Example 1 and Comparative Example 1 of the present invention;
[0060] Figure 6 This is a comparison chart of the capacity retention rate of the first cycle of button-type half-cells assembled with the core-shell structured positive electrode lithium-replenishing composite materials provided in Example 1 and Comparative Example 1 of the present invention, respectively. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0063] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0064] Example 1
[0065] This embodiment provides a positive electrode lithium supplement composite material with a core-shell structure, which includes Li2Ni 0.8 Cu 0.2 O2 positive electrode lithium supplement core material and coated on Li2Ni 0.8 Cu 0.2The monomolecular coating layer on the surface of the core material of the O2 positive electrode lithium supplement agent; the material of the monomolecular coating layer includes an amphiphilic compound, and the amphiphilic compound includes perfluorohexyl sulfonic acid. Among them, the amphiphilic compound and Li2Ni 0.8 Cu 0.2 The mass ratio of the core material of the O2 positive electrode lithium supplement agent is 0.025:1.
[0066] This embodiment also provides a method for replenishing lithium from the positive electrode composite material having a core-shell structure, such as Figure 1 As shown, the method comprises the following steps:
[0067] 0.01 g of commercially available perfluorohexane sulfonic acid was dissolved in 10 g of N-methylpyrrolidone to obtain an N-methylpyrrolidone solution with a mass concentration of 0.1 wt.%. 0.8 Cu 0.2 The O2 positive electrode lithium replenisher material (particle size of 2-10 μm) is added to a perfluorohexane sulfonic acid N-methylpyrrolidone solution with a mass concentration of 0.1wt.%. After stirring at a speed of 500r / min for 3 hours, the solution is filtered with a suction bottle, and the excess perfluorohexane sulfonic acid is continuously rinsed with N-methylpyrrolidone during the filtration process. The powder obtained in this way is collected and placed in a vacuum oven for vacuum drying at 70°C for 1 hour to obtain the positive electrode lithium replenisher composite material with a core-shell structure.
[0068] The positive electrode lithium supplement composite material with a core-shell structure prepared in this embodiment is as follows Figure 2 shown.
[0069] Example 2
[0070] This embodiment provides a positive electrode lithium supplement composite material with a core-shell structure, which includes Li2Ni 0.7 Cu 0.3 O2 positive electrode lithium supplement core material and coated on Li2Ni 0.7 Cu 0.3 The monomolecular coating layer on the surface of the core material of the O2 positive electrode lithium supplement agent; the material of the monomolecular coating layer includes an amphiphilic compound, and the amphiphilic compound includes perfluorohexyl sulfonic acid. Among them, the amphiphilic compound and Li2Ni 0.7 Cu 0.3 The mass ratio of the core material of the O2 positive electrode lithium supplement agent is 0.005:1.
[0071] This embodiment also provides a method for replenishing lithium from the positive electrode composite material having a core-shell structure, the method comprising the following steps:
[0072] 0.1 g of commercially available perfluorohexane sulfonic acid was placed in Figure 3 At the bottom of the device shown, 2g Li2Ni0.7 Cu 0.3 The O2 positive electrode lithium replenisher material (particle size of 2-10 μm) is suspended above the amphiphilic compound; the above container is placed in an oven, the heating temperature is 120°C, and the heating time is 6 hours, so that the amphiphilic compound is volatilized by heat, thereby spontaneously growing on the surface of the positive electrode lithium replenisher material to form a single molecule coating layer; after cooling to room temperature, the internal powder is stirred, and then heating, cooling and stirring are performed again, and the process is repeated 2-4 times to complete the coating, thereby obtaining the positive electrode lithium replenisher composite material with a core-shell structure.
[0073] Example 3
[0074] This embodiment provides a positive electrode lithium supplement composite material with a core-shell structure, which includes Li2Ni 0.6 Cu 0.4 O2 positive electrode lithium supplement core material and coated on Li2Ni 0.6 Cu 0.4 The monomolecular coating layer on the surface of the core material of the O2 positive electrode lithium supplement agent; the material of the monomolecular coating layer includes an amphiphilic compound, and the amphiphilic compound includes perfluorohexyl sulfonic acid. Among them, the amphiphilic compound and Li2Ni 0.6 Cu 0.4 The mass ratio of the core material of the O2 positive electrode lithium supplement agent is 0.03:1.
[0075] This embodiment also provides a method for replenishing lithium from the positive electrode composite material having a core-shell structure, the method comprising the following steps:
[0076] 0.1 g of commercially available perfluorohexane sulfonic acid was placed in Figure 4 In the sealed container shown, 2g Li2Ni 0.6 Cu 0.4 The O2 positive electrode lithium replenisher material (particle size is 2-10 μm) is placed in a porcelain boat and wrapped with an aluminum-plastic film on the outside, with a small opening in the upwind direction of the aluminum-plastic film; in a nitrogen atmosphere, the above device is placed in a tubular furnace, the heating temperature is 90°C, and the heating time is 5 hours, wherein the wind direction of the nitrogen atmosphere is parallel to the horizontal plane of the device, so that the amphiphilic compound is volatilized by heat and spontaneously grows on the surface of the material to form a coating layer, thereby obtaining the positive electrode lithium replenisher composite material with a core-shell structure.
[0077] Example 4
[0078] The difference between this embodiment and embodiment 1 is that the amphiphilic compound is replaced with an equal amount of dodecylbenzenesulfonic acid, and the rest is the same as embodiment 1.
[0079] Example 5
[0080] The difference between this embodiment and embodiment 1 is that the amphiphilic compound is replaced with an equal content of heptadecafluorodecyltrimethoxysilane, and the rest is the same as embodiment 1.
[0081] Example 6
[0082] The difference between this embodiment and embodiment 1 is that the amphiphilic compound is replaced by a combination of heptadecafluorodecyltrimethoxysilane and dodecylbenzenesulfonic acid in a mass ratio of 70:30, and the rest is the same as embodiment 1.
[0083] Example 7
[0084] The difference between this embodiment and embodiment 6 is that the amphiphilic compound is replaced by a combination of diphenylacetic acid and perfluorohexane sulfonic acid in a mass ratio of 80:20, and the rest is the same as embodiment 6.
[0085] Example 8
[0086] The difference between this embodiment and embodiment 6 is that the mass ratio of heptadecafluorodecyltrimethoxysilane to dodecylbenzenesulfonic acid is 50:50, and the rest is the same as embodiment 6.
[0087] Comparative Example 1
[0088] This comparative example provides a Li2Ni without coating treatment. 0.8 Cu 0.2 O2 positive electrode lithium supplement material.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 1 is that the material of the coating layer is replaced with an equal content of carbon material, and the rest is the same as Example 1.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the material of the coating layer is replaced with dodecylbenzene of the same content, and the rest is the same as Example 1.
[0093] Test conditions
[0094] The positive electrode lithium supplement composite materials provided in Examples 1 to 8 and Comparative Examples 1 to 3 were tested, and the test method was as follows:
[0095] The positive electrode lithium supplement composite material provided in the embodiment and the comparative example (initial state and after storage in air environment for 5 days), conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent for homogenization coating to make a positive electrode sheet. The prepared positive electrode sheet was assembled with a lithium metal electrode, a polypropylene (PP) separator and an electrolyte to obtain a 2032-type button battery for cycle performance testing, wherein the cycle test conditions were: 3 cycles at a rate of 0.1C (1C = 500mAh·g -1 , the charge and discharge cut-off voltage is 2-4.5V.
[0096] After the positive electrode lithium supplement composite materials provided in the examples and comparative examples were stored in an air environment for 5 days, the lithium supplement composite materials were 3 wt.% (based on LiNi 0.8 Co 0.1 Mn 0.1 The total mass of O2 is 100%) added to LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), and then mixed with conductive carbon black and polyvinylidene fluoride binder to make a positive electrode. Graphite was used as the negative electrode active material to make a negative electrode, and the full battery was assembled according to the N / P ratio of 1.04 for cycle performance testing. The cycle test conditions were: 3 cycles at a rate of 0.1C, and then 0.5C (1C = 200mAh g -1 , the charge and discharge cut-off voltage is 3-4.3V.
[0097] The test results are shown in Table 1:
[0098] Table 1
[0099]
[0100]
[0101] As can be seen from Table 1, it can be seen from Examples 1 to 3 of the present invention and Comparative Example 1 that the same amphiphilic compound but different preparation methods can all be used to obtain a positive electrode lithium supplement composite material with high environmental stability and high ion conductivity, further indicating that the present invention provides a technical solution with low process requirements and the ability to improve the electrochemical performance of lithium ion batteries.
[0102] From Examples 1 and 4 to 5, it can be seen that Example 4 has the same hydrophilic head group as Example 1, but the hydrophobic tail is a full alkyl chain; while Example 5 has a hydrophobic tail group with a similar structure to Example 1, but the hydrophilic head group is a silane group; the hydrophobicity of the hydrophobic tail of the full alkyl chain in Example 4 is worse than that of the hydrophobic tail of the perfluoroalkyl chain in Example 1, and the lithium ion diffusion coefficient of the silane hydrophilic head group in Example 5 is not as good as the lithium ion diffusion coefficient of the sulfonic acid hydrophilic head group in Example 1, so the comprehensive performance of the lithium ion battery assembled by the two is reduced. It can be seen that the present invention is beneficial to improve the environmental stability and cycle performance of lithium ion batteries by selecting tail groups with strong hydrophobic ability and head groups with high lithium ion diffusion coefficients.
[0103] It can be seen from Examples 1 and 6 to 7 that the present invention combines and modifies amphiphilic compounds having different preferred types of hydrophilic head groups and hydrophobic tail groups. Compared with the use of a single type of amphiphilic compound for coating, the coating layer generated by coating with a combination of different preferred types of amphiphilic compounds can be denser and have stronger ion conductivity, so that the comprehensive performance of the obtained lithium-ion battery is higher.
[0104] It can be seen from Examples 6 to 7 and Example 8 that the mass ratio of heptadecafluorodecyltrimethoxysilane and dodecylbenzenesulfonic acid used in Example 8 is not within the preferred range of the present invention, which makes the positive electrode lithium replenisher material have a poor hydrophobic effect and a high polarization, thereby reducing the overall performance of the prepared lithium ion battery. This further shows that the present invention is beneficial to improving the environmental stability of the coating layer and the cycle performance of the prepared lithium ion battery by regulating the mass ratio of fluorinated silane molecules and alkyl sulfonic acid molecules within the preferred range.
[0105] It can be seen from Example 1 and Comparative Example 1 that Comparative Example 1 provides Li2Ni without coating treatment. 0.8 Cu 0.2 O2 positive electrode lithium supplement material, such as Figure 5 It can be seen that the residual alkali content of the positive electrode lithium supplement material after being modified by the specific type of monomolecular coating layer provided by the present invention is significantly reduced; and Figure 6 It can be seen that the first cycle capacity retention rate of the button half-cell obtained after the powder was placed for 5 days was significantly improved, proving that the positive electrode lithium replenishing composite material provided by the present invention has strong hydrophobicity and good environmental stability. It can be seen that the present invention uses amphiphilic compounds to self-assemble and coat the positive electrode lithium replenishing agent material, and then adds it to the battery system, so that the obtained lithium ion battery has better cycle performance.
[0106] It can be seen from Example 1 and Comparative Example 2 that Comparative Example 2 uses conventional carbon material as the coating layer, and the environmental stability cannot achieve the full technical effects of the present invention. It can be seen that the present invention uses a tail group with strong hydrophobicity as the modified interface, so that the obtained positive electrode lithium supplement composite material powder has excellent hydrophobic properties, thereby making the lithium ion battery have better cycle performance.
[0107] It can be seen from Example 1 and Comparative Example 3 that Comparative Example 3 is modified only with dodecylbenzene having a hydrophobic function, and it has only a physical adsorption effect with the surface of the positive electrode lithium supplement material. Although it has a certain hydrophobic effect, it cannot guarantee a better ion conduction property. This further shows that the present invention uses a specific type of amphiphilic compound as a coating source, which can ensure that it has good environmental stability while also having high ion superconductivity, so that the obtained lithium ion battery has a longer cycle life.
[0108] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode lithium supplement composite material with a core-shell structure, characterized in that: The positive electrode lithium supplement composite material with a core-shell structure comprises a positive electrode lithium supplement core material and a monomolecular coating layer coated on the surface of the positive electrode lithium supplement core material; The material of the monomolecular coating layer includes an amphiphilic compound, and the amphiphilic compound includes a hydrophilic head and a hydrophobic tail. The structural formula of the amphiphilic compound is shown in Formula I: XYZ Formula I; Wherein, the structure of X contains any one or a combination of at least two of a carboxylate group, a sulfonate group, a sulfate group or a silane group; Y is selected from at least one of a single bond, a hydrocarbon group or a nitrogen heterocycle; Z is at least one selected from a substituted or unsubstituted hydrocarbon group, a substituted or unsubstituted thiol hydrocarbon group, or a substituted or unsubstituted aryl group.
2. The positive electrode lithium supplement composite material with a core-shell structure according to claim 1, characterized in that: The structure of X comprises a combination of a silane group and a sulfonate group, or a combination of a carboxylate group and a sulfonate group; Preferably, Y is selected from a single bond or an alkyl group; Preferably, Z is selected from at least one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted sulfanyl group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, or a substituted or unsubstituted phenylsilyl group; Preferably, the substituted group includes at least one of a halogen atom, a nitrogen heterocycle, an aryl group or an alkyl group.
3. The positive electrode lithium supplement composite material with a core-shell structure according to claim 1 or 2, characterized in that: The amphiphilic compound is selected from any one or a combination of at least two of polyphenylmethylsilane, phenyltris(trimethylsiloxy)silane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, pentafluorononyltrimethoxysilane, pentafluorononyltriethoxysilane, tridecafluorooctyltrimethoxysilane or tridecafluorooctyltriethoxysilane; Preferably, the amphiphilic compound is selected from any one or a combination of at least two of 3-fluorobenzene methane sulfonic acid, benzene sulfonic acid, 4-fluorobenzene sulfonic acid, dodecylbenzene sulfonic acid, undecylbenzene sulfonic acid, decanylbenzene sulfonic acid, pentafluorobenzene sulfonic acid, perfluorohexyl sulfonic acid, sodium dodecyl sulfate, sodium tetradecyl sulfate, ammonium dodecyl sulfate or sodium decyl sulfate; Preferably, the amphiphilic compound is selected from any one or a combination of at least two of stearic acid, tryptophan, diphenylacetic acid, 2-[(difluoromethyl)sulfanyl]pyridine-3-carboxylic acid or (2S,4R)-4-((tert-butyldiphenylsilyl)oxy)pyrrolidine-2-carboxylic acid.
4. The positive electrode lithium supplement composite material with a core-shell structure according to claim 3, characterized in that: When the amphiphilic compound comprises a combination of fluorinated silane molecules and alkyl sulfonic acid molecules, the mass ratio of the fluorinated silane molecules to the alkyl sulfonic acid molecules is (60-90):(10-40), preferably (65-85):(15-35).
5. The positive electrode lithium supplement composite material with a core-shell structure according to any one of claims 1 to 4, characterized in that: The chemical formula of the core material of the positive electrode lithium supplement is Li a M x N 1-x O c , wherein 2≤a≤6, 0≤x≤1, 1≤c≤6, and M includes Fe or Ni, and N includes at least one of Mg, Al, Si, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Sn or W; Preferably, the hydrophilic head is at least partially bonded to the surface of the positive electrode lithium supplement core material.
6. The positive electrode lithium supplement composite material with a core-shell structure according to any one of claims 1 to 5, characterized in that: The mass ratio of the material of the monomolecular coating layer to the core material of the positive electrode lithium supplement agent is (0.001-0.05):1, preferably (0.005-0.03):
1.
7. A method for preparing a positive electrode lithium supplement composite material having a core-shell structure according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: The amphiphilic compound is coated on the positive electrode lithium replenishing agent material by a liquid phase method and / or a gas phase method to obtain the positive electrode lithium replenishing composite material with a core-shell structure, wherein the amphiphilic compound includes a hydrophilic head and a hydrophobic tail.
8. The method according to claim 7, characterized in that The liquid phase method comprises mixing an amphiphilic compound, a positive electrode lithium replenishing agent material and a solvent, and removing the solvent after the reaction to obtain the positive electrode lithium replenishing composite material having a core-shell structure; Preferably, the gas phase method comprises placing the positive electrode lithium replenisher material in a system containing amphiphilic compound vapor, and cooling the system to form the positive electrode lithium replenisher composite material having a core-shell structure.
9. A positive electrode, characterized in that The positive electrode comprises a positive electrode active material and a lithium supplement material, wherein the lithium supplement material comprises a positive electrode lithium supplement composite material having a core-shell structure according to any one of claims 1 to 6; Preferably, based on the total mass of the positive electrode active material being 100%, the mass percentage of the lithium supplement material is 2 wt.% to 8 wt.%.
10. A secondary battery, characterized in that: The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode includes the positive electrode according to claim 9.
Citation Information
Cited By
High-capacity positive electrode lithium supplement agent and preparation method and application thereof
CN122619805A